Federalism and Intergovernment Coordination - Fenna, Alan (Sage Publications, 2012)
Federalism is a distinct governmental form with its own particular impact on public administration and policy and programme coordination between governments. In particular, it is a system where intergovernmental relations and coordination occur within a constitutionally structured relationship between central governments and the constituent units. At the same time, no two federations are the same, and each tends to operate in its own distinctive manner. This follows from differences in approaches to the division of powers and the form of government; as well as the degree to which there is an underlying federal society. The degree of entanglement between levels of government in contemporary federations puts a premium on cooperation and coordination that is accomplished through a variety of institutions and processes and which spans political and administrative spheres. Attempts to characterize these realities have generated a range of concepts, including cooperative federalism, collaborative federalism, administrative federalism, regulatory federalism, coercive federalism, executive federalism, pragmatic federalism, adaptive federalism, opportunistic federalism, conditional federalism, and much more.